Heterocyclic synthesis with nitriles: synthesis of pyrazolopyrimidine and pyrazolopyridine derivatives - Salaheldin, Abdellatif M. (2009)
The reaction of N1-substituted-5-amino-4-cyanopyrazoles with malononitrile and diethylmalonate occurs with formation of 6-substituted pyrazolo[3,4-d]pyrimidines, and pyrazolo[3,4-b]pyridines respectively. The structures of the products and conceivable mechanisms are discussed.